Multi-state Diagnostics for Distributed Radio Direction Finding System - Aminev, Dmitry; Zhurkov, Alexander; Kozyrev, Dmitry (Distributed Computer and Communication Networks, 2017)
We consider a distributed Radio Direction Finding System (RDFS) and the structure of its hardware. A classical diagnostic model of the distributed RDFS according to the binary criterion is presented, which includes diagnostic graphs and a set of tests. We propose a theoretical basis for diagnosing of the distributed RDFS according to the n-dimensional criterion. An example of implementation of the diagnostic approach to the distributed RDFS for states “failure”, “deterioration”, “normal” is presented.